1978
DOI: 10.1099/00221287-107-1-37
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Incubation Media on the Recovery of Escherichia coli K12 Heated at 52 0C

Abstract: 37The exposure of exponentially grown Escherichia coli ~1 2 to 52 "C for 30 min in Tris/Mg2+ buffer resulted in a considerable loss of viability when plated on tryptone agar. When such heated bacteria were held at 37 "C for 2 h in tryptone broth before plating on tryptone agar, there was a significant increase in viability. Thus, heat damage was repaired in tryptone broth but not on tryptone agar. Recovery was greater in tryptone broth than in synthetic medium. In tryptone broth, recA or polA mutants also reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…When cells are exposed to stressful environments, e.g., cooling, heating, radiation, or desiccation, cellular functions may be impaired. It has been observed that for some cells, preincubation in broth or liquid medium for some time after exposure to the stress may help repair the injuries (1,8,15,23); however, others doubt its effectiveness (7). In the present work, preincubation did not improve the recovery of cryopreserved BCG cells from cryoinjury.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…When cells are exposed to stressful environments, e.g., cooling, heating, radiation, or desiccation, cellular functions may be impaired. It has been observed that for some cells, preincubation in broth or liquid medium for some time after exposure to the stress may help repair the injuries (1,8,15,23); however, others doubt its effectiveness (7). In the present work, preincubation did not improve the recovery of cryopreserved BCG cells from cryoinjury.…”
Section: Discussionmentioning
confidence: 43%
“…Common cryopreservation media, the effect of a cryoprotective agent (glycerol), and the cooling rate were studied. It has been suggested that transient incubation of cells in broth medium after exposure to stress environments, such as heating, freezing/thawing, or UV light, helps to repair the injury for some cell types (1,8,15,23). Therefore, the effect of transient incubation (preincubation) on cryopreserved BCG cells was also explored.…”
mentioning
confidence: 99%
“…Most Probable Number (MPN) techniques were applied in some investigations. Procedures for repair of heat-injured bacteria were studied by [1,127,116,157,158,63]. …”
Section: Experimental Conditionsmentioning
confidence: 99%
“…For example, the D 60 and Z values of E. coli were reported to range from 35 $ 42 s to 5.9 $ 6.1 C (95% confidence interval). [29][30][31][32][33][34][35][36][37][38] The D 60 and Z values of E. faecium ranged from 1.0 Â 10 3 $ 1.3 Â 10 3 s to 8.8 $ 11 C (95% confidence interval). [39][40][41][42][43][44][45][46] The effects of SOAP on water temperature and R D with respect to lens structure (e.g., hemispherical and semi cylindrical lens) are also investigated in Figure 3 temperature of the hemispherical lens at the focal point is higher than that of the semi cylindrical lens by about 8 C, the hemispherical lens shows about 3% higher R D in the case of E. faecium (Figure 3(c)).…”
Section: Solar Disinfection Of Pathogens In Soapmentioning
confidence: 99%